Food tourism destinations' imagery processing model. Issue 6 (17th May 2019) - Cardoso, Lucília; Araújo Vila, Noelia; de Araújo, Arthur Filipe; Dias, Francisco
Abstract : Purpose: Over the last two decades, the concept of destination imagery (DY) has gained relevance in the academic literature due to its central role in the tourists' destination choice process. However, there is still much to be explored within this topic, especially concerning DY processing. More specifically, the way external stimuli are processed in tourists' memory is still unexplored. In this context, the purpose of this paper is to examine how DY is processed in individuals' memories upon the reception of verbal stimuli related to food tourism destinations. Design/methodology/approach: Through an online multilingual survey, imagery elements associated with European and Asian tourists' favourite food tourism destinations were collected. Through a categorical content analysis, tourists' perceptions were classified within Echtner and Ritchie's (1993) tri-dimensional model's dimensions. Results were examined against previous theories on DY. Moreover, a comparative analysis between the imagery of food tourism destinations held by Europeans and Asians tourists was carried out. Findings: Results show that DY processing, when triggered by a food tourism destination stimulus, leans towards the holistic dimension, which reinforces previous theories on the topic, such as the very definition of destination image (DI), as well as the role of food on destination image. Moreover, differences were found between the type of destinations and the imagery processed by European and Asian tourists. Research limitations/implications: The study is based on a significant data set, which comprised 1, 186 responses, representativeness within the research universe cannot be assured. Although relatively equivalent volumes of data were collected from each of the two continents, there are significant discrepancies among the proportions of respondents from different countries within those two groups. Additionally, our theoretical model requires further validation through hypothesis verification procedures. This work builds theory, rather than testing it. In this context, it opens a research avenue for future studies adopting a more positivistic philosophical stance to research, which could submit the theories provided here to the scrutiny of rigorous, hypothesis testing, quantitative methods. Practical implications: This paper provides an initial idea for destination managers about which aspects to highlight in their marketing campaigns. This particularly applies to destinations to which ethnic food is a relevant part of the tourist appeal, and whose managers intend to attract repeat visitors. Social implications: The present study's findings imply a series of suggestions for tourism practitioners. First, they provide an initial idea for destination managers about which aspects to highlight in their marketing campaigns. Originality/value: The present study represents a first initiative of building a theoretical model of food tourism destinations' imagery processing. Findings also provide original theoretical contributions to the concept of DY and lead to relevant managerial insights, particularly, into destinations aiming at attracting repeat, food-oriented tourists.